Exploring the meanings of professional activism. Issue 2 (15th March 2021) - Costa, Ana L.; Vaz, Henrique; Menezes, Isabel
ABSTRACT: There is growing recognition of the relevance of political mobilization in educational, social and community work, particularly when working with people in situations of vulnerability. However, there is also a scarcity of research that describes and explains professionals' political involvement and mobilization and allows them to share their activist experiences, to inspire others and legitimate this crucial dimension of their work. This qualitative study explores the meanings of "professional activism" for professionals working in Portugal, who are recognized for developing relevant political work related to their profession. A net of themes – Taking Sides, Utopian Ideal, Sense of (In)Justice and Praxis – portrays professional activism as a praxis that promotes and is guided by a sense of (in)justice, which demands a positioning in defense of the people with whom professionals work, leading to interventions oriented by/for a utopian ideal of transformation.